Lithium intercalation edge effects and doping implications for graphite anodes. Issue 16 (9th April 2020) - Peng, Chao; Mercer, Michael P.; Skylaris, Chris-Kriton; Kramer, Denis
Abstract : The interface between the electrolyte and graphite anodes plays an important role for lithium (Li) intercalation and has significant impact on the charging/discharging performance of Lithium-Ion Batteries (LIBs). Abstract : The interface between the electrolyte and graphite anodes plays an important role for lithium (Li) intercalation and has significant impact on the charging/discharging performance of Lithium-Ion Batteries (LIBs). However, atomistic understanding of interface effects that would allow the interface to be rationally optimized for application needs is largely missing. Here we comprehensively study the energetics of Li intercalation near the main non-basal surfaces of graphite, namely the armchair and zigzag edges. We find that edge sites at both surfaces bind Li more strongly than in the bulk of graphite. Therefore, lithiation of these sites is expected to proceed at higher voltages than in the bulk. Furthermore, this effect is significantly more pronounced at the zigzag edge compared to the armchair edge due to its unique electronic structure. The "peculiar" topologically stabilized electronic surface state found at zigzag edges strongly interacts with Li, thereby changing Li diffusion behavior at the surface as well. Finally, we investigate boron (B)/nitrogen (N) doping as a promising strategy to tune the Li intercalation behavior at both edge systems, which could lead to enhanced intercalation kinetics in B/N doped graphite anodes.